THE STUDY OF STUDENTS’ SPEAKING ANXIETY IN THE POST-PANDEMIC ERA - Nadiyya Zulfa; Ahmad Syafi'i (STKIP Al Hikmah Surabaya, 2022)
Since the COVID 19 outbreak, distance learning is the best way to continue the school activity. the teacher posted the lesson and assignment and the students can access those in the E-Learning. This condition made the speaking activity between students and teacher drastically reduced, and that can potentially make the speaking anxiety of the students increased. This study is aimed to explore the level of speaking anxiety in the post online learning, as well as the factors and the strategies in overcoming the speaking anxiety.